Exploring Trainee Teachers’ Academic Self-Concept, Academic Effort and Academic Confidence with Academic Achievement - Naseer, Naila; Mariam Rafique (Journal of Digital Scholarship in Archives and Information, 2025)
Background: Distance learning requires teachers who are adequately trained and possess strong psychological constructs, including academic self-concept, academic effort, and academic confidence, to meet diverse student needs. These psychological factors are essential for effective teaching and learning, especially in remote educational settings.Aims: This study aims to examine the relationship between prospective teachers’ academic effort and academic confidence with their academic performance across different achievement groups.Method: The study involved prospective teachers enrolled in two teacher-training programs: M.Ed (373 participants) and B.Ed (427 participants). A standardized research instrument was used to measure academic effort, academic self-concept, and academic confidence. Data were analyzed to compare differences among low-, average-, and high-achieving groups.Results: The analysis revealed significant differences in academic effort, academic self-concept, and academic confidence among the three academic achievement groups. High achievers demonstrated stronger psychological constructs compared to average and low performers.Conclusions: The study suggests that collaborative projects and teamwork integrating high, average, and low achievers can enhance the skills and expertise of all groups. Such collaboration may strengthen prospective teachers’ academic self-concept and academic confidence, contributing to improved overall academic performance.